2018
DOI: 10.1002/mop.31694
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional holographic imaging using data collected over cylindrical apertures

Abstract: The previously proposed near‐field holographic imaging algorithms are based on the data collected over rectangular apertures. In this letter, we propose an approach for three‐dimensional near‐field holographic imaging with data collected over cylindrical apertures. Circular deconvolution is employed to deal with the periodicity of the functions along the azimuthal direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The following derivation of QMH applies to planar apertures (along x, y, range along z), though formulations of QMH for cylindrical apertures are also available [40], [41]. QMH relies on the measurements of three separate objects for image reconstruction, the reference object (RO), the CO, and the OUT.…”
Section: A Measurement Setupmentioning
confidence: 99%
“…The following derivation of QMH applies to planar apertures (along x, y, range along z), though formulations of QMH for cylindrical apertures are also available [40], [41]. QMH relies on the measurements of three separate objects for image reconstruction, the reference object (RO), the CO, and the OUT.…”
Section: A Measurement Setupmentioning
confidence: 99%
“…This has been notified in the previous works as well (e.g., see ref. [18]). Also, it is observed that the quality of the imaging improves when using double frequency data compared to single frequency data.…”
Section: D Imaging Of Larger Objectsmentioning
confidence: 99%
“…To address the above-mentioned needs for fast and robust near-field microwave imaging, holographic imaging techniques have been adapted for such applications. In near-filed holographic microwave imaging, back-scattered signals are collected over rectangular [14][15][16] or cylindrical [17,18] apertures and reconstruction can be performed to volumetrically image the dielectric bodies. A summary of near-field microwave holographic imaging techniques can be found in ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wide-band SAR imaging has been used to produce three-dimensional (3D) images of the vertical cracks/flaws in fat and curved HDPE pipes [8]. Recently, SAR-based imaging techniques have been extended to the near-field applications where the distance between the measuring antennas and the imaged object is small (e.g., see [9,10]). Thus, these techniques can be called near-field holographic imaging techniques where the information related to a specific imaging system is obtained a priori through the measurement of the so-called point-spread functions (PSFs) [11].…”
Section: Introductionmentioning
confidence: 99%